(untitled) (American Journal of Islam and Society, 1991)
The Qur’an, being central to both the Islamic faith and its practice, has been studied in a plethora of orientalist writings-ranging from such a crudely polemical one as Alexander Ross’s English translation of the Qur’an entitled The Alcoran of Mahomet . . . for the Satisfaction for all those who Desire to look into the Turkish Vanities (1649) to those with scholarly pretensions and claiming to be "objective" studies, such as Noldeke’s Geschichte des Qorans (1860), Goldziher’s Die Richtungen der islamischen Koranauslesung (1920), Bell’s The Quran translated with a Critical Rearrangement of the Surahs (1937-39), Wansbrough’s Quranic Studies (1977), and Burton’s The Collection of the Quran (1977). The book under review, first published in 1983, recounts the full tock of the orientalists’ misconceptions, down the ages, about the Qur’an-their outlandish theories about its authorship (pp. 7-18), their assaults on its textual history and its arrangement (pp. 52-63), their brazen attempts at twisting its meaning in their Qur’an translations (pp. 64-92), and their bizzare views on abrogation in the Qur’an (pp. 93-104). Khalifa deserves every credit for assembling so much information. What is more remarkable is that it is followed by a stout refutation of these allegations about the form and contents of the Qur’an and an extensive, authentic exposition of the Qur’anic teachings, concepts, and morals, all of which constitutes the second part of the book (pp. 111-205). In elucidating the Qur’anic worldview, Khalifa’s discussion is subtle, in large part persuasive, tenaciously pursued, and well presented. Appended to the book are two highly informative appendices on the order of the Qur’an’s surahs. This well-intentioned and detailed scholarly study, however, does not really succeed in delivering what its title promises. In discussing the orientalists’ ventures into establishing the chronology of Qur’anic surahs, Khalifa says little about Gustav Fli:lgel’s Corani Textus Arabiscus (1834) and the theories propounded by Grimme and Hirschfield’s New Researches in the Composition and Exegesis of the Quran (1902). More serious is the lack of any reference to a host of orientalists’ writings on the philological and lexical aspects of the Qur’an, namely Baljon’s Modern Muslim Quran Interpretation (1961), Torrey’s The Commercial-Theological Terms in the Quran (1892), Watt’s ...